Cursing with God : the imprecatory psalms and the ethics of Christian prayer - Laurence, Trevor (Waco : : Baylor University Press, 2022)
"Examines the moral intelligibility of the imprecatory Psalms and proposes a model for how Christians can ethically incorporate them into their worship"--